2021
DOI: 10.1177/09596836211019115
|View full text |Cite
|
Sign up to set email alerts
|

Holocene hydroclimate reconstruction based on pollen, XRF, and grain-size analyses and its implications for past societies of the Korean Peninsula

Abstract: The dynamics of the East Asian Summer Monsoon (EASM) and their link to past societies during the Holocene are topics of growing interest. In this study, we present results of pollen, geochemistry, and grain-size analyses from the STP18-03 core sampled from Miryang in the Korean Peninsula, which spans ca. 8.3–2.3 ka BP. In-phase relationships of these proxies revealed an imprint of the Holocene Climate Optimum (HCO) during the early to mid-Holocene and subsequent drying toward the late-Holocene in accordance wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…The results of previous pollen studies in the Korean peninsula have suggested that the climate was comparatively dry during periods when WTP SSTs cooled because of long-term El Niño-Southern Oscillation-type variations 2 , 19 22 . The frequency of El Niño events may have increased, leading to reduced WTP SSTs and a smaller amount of atmospheric water vapor above the oceanic source region where the East Asian summer monsoon originates.…”
Section: Resultsmentioning
confidence: 99%
“…The results of previous pollen studies in the Korean peninsula have suggested that the climate was comparatively dry during periods when WTP SSTs cooled because of long-term El Niño-Southern Oscillation-type variations 2 , 19 22 . The frequency of El Niño events may have increased, leading to reduced WTP SSTs and a smaller amount of atmospheric water vapor above the oceanic source region where the East Asian summer monsoon originates.…”
Section: Resultsmentioning
confidence: 99%
“…Human activity as a generator of flooding, or at least as an enhancer of flood events, during the middle to late Holocene needs to be considered. Recent studies have tested the possible relationship between population and climate change during the early to late Holocene (Oh et al, 2017; Park et al, 2021). Based on the comparison between pollen analyses from Miryang area in Korea and summed probability distributions of radiocarbon dates from archeological sites in Korea as a proxy for change in population levels, Park et al (2021) suggested that dry periods correspond to lower population levels during the early to late Holocene and that human societies were vulnerable to climate changes.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have tested the possible relationship between population and climate change during the early to late Holocene (Oh et al, 2017; Park et al, 2021). Based on the comparison between pollen analyses from Miryang area in Korea and summed probability distributions of radiocarbon dates from archeological sites in Korea as a proxy for change in population levels, Park et al (2021) suggested that dry periods correspond to lower population levels during the early to late Holocene and that human societies were vulnerable to climate changes. Despite this climatic influence on human activity, it seems difficult to separate the human role (e.g., through deforestation) as a trigger of flooding from natural climate changes in detail due to lack of case studies showing human activity and resultant flooding events during the early to late Holocene.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the exact cause of the culture's rapid decline remains unknown. Recent paleoclimate data from the Korean Peninsula suggest that the cause was climate deterioration around 2800 and 2300 years ago, likely related to changes in WTP SSTs 2,21,54 .…”
Section: Societal Response To Climate Changementioning
confidence: 99%